Suicidal behaviour amid first wave of COVID-19 pandemic in Malaysia: Data from the COVID-19 mental health international (COMET-G) study - Razali, Salmi; Saw, Jo Anne; Hashim, Nurul Azreen; Raduan, Nor Jannah Nasution; Tukhvatullina, Dina; Smirnova, Daria; Fountoulakis, Konstantinos N. (Frontiers in Psychiatry, 2022)
During the COVID-19 pandemic, numerous social and life changes were implemented to curb the spread of the disease. The effect of lockdown and isolation predisposed the general population to various psychological health concerns. The existing determinants of suicidal behaviour were further added with social isolation, financial stress, depression, and other pandemic-related stressors. Hence, our study aimed to investigate suicidal behaviour and the associated factors among Malaysians during the COVID-19 pandemic. It is a cross-sectional online questionnaire survey that used convenient sampling where the survey was disseminated to the public via Google Forms through social media during the first wave of COVID-19 pandemic in Malaysia. This study is also part of a large international COVID-19 mental health international study for the general population (COMET-G). This research revealed concerns about issues related to suicidal behaviours during the beginning of the Covid-19 pandemic. Suicidal behaviours were associated with depression, sex, marital status, educational level, employment type, residential area, number of people living together, number of children and family dynamic. The damages from psychological, social and economic perspectives resulting from the pandemic will undoubtedly needing more time to improve. Future prevention and protection are needed especially to the highly at risk group on top of the general population in any future unforeseen circumstances of pandemic.